DAMPAK RISIKO PAJAK DAN FAKTOR LAIN TERHADAP BIAYA MODAL PERUSAHAAN MANUFAKTUR - Dewi Kusuma Wardani; Safira Widya Putriane (Media Riset Akuntansi, Auditing & Informasi, 2020)
This research examined tax risk, audit quality, institutional ownership, and firm size on cost of capital. We used listed manufacture companies in Indonesia during 2013-2017. Based on purposive sampling method was obtained 48 companies. Tax risk variable is proxy by CETR, audit quality is proxy by KAP Big 4, institutional ownership uses a percentage of the amount spent by reserves, firm size by Ln total asset. The dependent variable is proxy by the cost of debt. We used multiple linear regression method. The research found that the tax risk and audit quality have negatif effect on cost of capital. While, institutional ownership and firm size do not have significant effect on the cost of capital.